2022
DOI: 10.3389/fimmu.2022.1014861
|View full text |Cite
|
Sign up to set email alerts
|

m6A methylation regulators as predictors for treatment of advanced urothelial carcinoma with anti-PDL1 agent

Abstract: Purpose: Immune checkpoint blockade agents were shown to provide a survival advantage in urothelial carcinoma, while some patients got minimal benefit or side effects. Therefore, we aimed to investigate the prognostic value of m6A methylation regulators, and developed a nomogram for predicting the response to atezolizumab in urothelial carcinoma patients.Methods: A total of 298 advanced urothelial carcinoma patients with response data in the IMvigor210 cohort were included. Differential expressions of 23 m6A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Several studies indicated that IGF2BP3 was positively associated with the expression of PD-L1 in immune cells ( Cui et al, 2022 ), while FTO was just the opposite ( Deng et al, 2022 ). Kong et al (2022) found that in bladder cancer, the expression of HNRNPA2B1, FMR1, IGF2BP1, IGF2BP3, and YTHDF2 were significantly upregulated in the anti-PD-1 immunotherapy response group, while FTO expression was significantly downregulated. They also constructed a nomogram to predict the responsiveness of patients to atezolizumab monotherapy ( Kong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies indicated that IGF2BP3 was positively associated with the expression of PD-L1 in immune cells ( Cui et al, 2022 ), while FTO was just the opposite ( Deng et al, 2022 ). Kong et al (2022) found that in bladder cancer, the expression of HNRNPA2B1, FMR1, IGF2BP1, IGF2BP3, and YTHDF2 were significantly upregulated in the anti-PD-1 immunotherapy response group, while FTO expression was significantly downregulated. They also constructed a nomogram to predict the responsiveness of patients to atezolizumab monotherapy ( Kong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
“… Kong et al (2022) found that in bladder cancer, the expression of HNRNPA2B1, FMR1, IGF2BP1, IGF2BP3, and YTHDF2 were significantly upregulated in the anti-PD-1 immunotherapy response group, while FTO expression was significantly downregulated. They also constructed a nomogram to predict the responsiveness of patients to atezolizumab monotherapy ( Kong et al, 2022 ). But there were also other studies showing that FTO expression level was higher in bladder cancer patients who did not respond to immunotherapy ( Deng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The use of m6A regulator inhibitors in enhancing ICB therapies has been extensively explored in recent studies [ 335 , 336 ]. m6A methylases play a crucial role in modulating the expression levels of PD-L1 and enhancing tumor sensitivity to anti-PD-1 and anti-CTLA-4 therapies, thereby improving the outcomes of ICB treatments [ 50 , 234 , 337 ].…”
Section: Classification Of Rna Methylationmentioning
confidence: 99%
“…Dysregulation of m6A has been linked to cancer progression (25)(26)(27)(28)(29)(30). The effect of m6A-related genes on cancers has been widely studied, such as breast cancer (31), gastrointestinal cancer (32), urothelial carcinoma (33), gastric cancer (34). In pancreatic cancer, ALKBH5-mediated upregulation of DDIT4-AS1 maintains pancreatic cancer stemness and inhibits chemosensitivity through activation of the mTOR pathway (35).…”
Section: Introductionmentioning
confidence: 99%